Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the system of equations using the substitution method, we start by expressing one variable in terms of the other using one of the given equations. In this case, equation 2 provides an expression for [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]:
1. Write equation 2:
[tex]\[ y = x - 1 \][/tex]
2. Substitute this expression for [tex]\( y \)[/tex] into equation 1, which is:
[tex]\[ 2x + 3y = 12 \][/tex]
Substituting [tex]\( y = x - 1 \)[/tex] into equation 1:
[tex]\[ 2x + 3(x - 1) = 12 \][/tex]
3. Distribute [tex]\( 3 \)[/tex] inside the parentheses:
[tex]\[ 2x + 3x - 3 = 12 \][/tex]
4. Combine like terms:
[tex]\[ 5x - 3 = 12 \][/tex]
5. Solve for [tex]\( x \)[/tex] by isolating [tex]\( x \)[/tex]:
[tex]\[ 5x - 3 + 3 = 12 + 3 \][/tex]
[tex]\[ 5x = 15 \][/tex]
[tex]\[ x = \frac{15}{5} \][/tex]
[tex]\[ x = 3 \][/tex]
6. Now that we have [tex]\( x \)[/tex], use equation 2 to find [tex]\( y \)[/tex]:
[tex]\[ y = x - 1 \][/tex]
Substitute [tex]\( x = 3 \)[/tex]:
[tex]\[ y = 3 - 1 \][/tex]
[tex]\[ y = 2 \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ (x, y) = (3, 2) \][/tex]
1. Write equation 2:
[tex]\[ y = x - 1 \][/tex]
2. Substitute this expression for [tex]\( y \)[/tex] into equation 1, which is:
[tex]\[ 2x + 3y = 12 \][/tex]
Substituting [tex]\( y = x - 1 \)[/tex] into equation 1:
[tex]\[ 2x + 3(x - 1) = 12 \][/tex]
3. Distribute [tex]\( 3 \)[/tex] inside the parentheses:
[tex]\[ 2x + 3x - 3 = 12 \][/tex]
4. Combine like terms:
[tex]\[ 5x - 3 = 12 \][/tex]
5. Solve for [tex]\( x \)[/tex] by isolating [tex]\( x \)[/tex]:
[tex]\[ 5x - 3 + 3 = 12 + 3 \][/tex]
[tex]\[ 5x = 15 \][/tex]
[tex]\[ x = \frac{15}{5} \][/tex]
[tex]\[ x = 3 \][/tex]
6. Now that we have [tex]\( x \)[/tex], use equation 2 to find [tex]\( y \)[/tex]:
[tex]\[ y = x - 1 \][/tex]
Substitute [tex]\( x = 3 \)[/tex]:
[tex]\[ y = 3 - 1 \][/tex]
[tex]\[ y = 2 \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ (x, y) = (3, 2) \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.